'Do I want to work for him?' The effects of variations in content, source, and age of managers' social networking information on prospective job applicants' attitudes. (9th July 2021) - Ballweg, Christopher; Ross, William H.; Secchi, Davide
Does personal social networking website (SNW) content influence prospective job applicant reactions to their probable supervisor? A 2 × 2 × 2 design varied whether: 1) the prospective manager's SNW comments emphasised alcohol abuse vs. professional activities; 2) his friends emphasised alcohol vs. professional activities; 3) SNW information was five days vs. five years old. Findings indicated that alcohol-oriented information on personal SNWs - whether posted by the manager or by the manager's friends - negatively affected attitudes toward the manager. Information posted by the manager's friends had little impact on a willingness to apply or interview for the position. However, alcohol-oriented information posted by the manager decreased prospective applicants' willingness to interview for the position; they also wanted a higher salary to work for such a manager. Congruence of information only had effects if both the manager and friends emphasised professionalism. Age of website information had little effect on ratings.